Annual booster vaccination and the risk of equine influenza to Thoroughbred racehorses. (12th February 2020) - Gildea, Sarah; Lyons, Pamela; Lyons, Rachel; Gahan, Jacinta; Garvey, Marie; Cullinane, Ann
Abstract: Background: Equine influenza (EI) outbreaks occurred among horses on four racing yards (two National Hunt, one Flat, one mixed National Hunt racing/breeding yard) in Ireland within a 4‐week period. Objectives: To carry out a detailed analysis of racing yards affected in order to identify the source of infection and monitor virus spread among a vaccinated population. Study design: Observational field study. Methods: Epidemiological and vaccination data along with repeat clinical samples were collected from 118 horses on four premises. Results: Failure to implement appropriate biosecurity measures following the introduction of new arrivals and the return of horses from equestrian events contributed to disease spread as did the movement of horses within premises. Mixing of racing and non‐racing populations with inadequate vaccination histories also facilitated virus transmission. The index case(s) on all premises was vaccinated in accordance with the Turf Club rules. Vaccine breakdown was observed across all products in 27/80 horses (33.8%) with an up‐to‐date vaccination record. Eighteen of the 27 (66.7%) horses had not received a booster vaccination within the previous 6 months and 10 (37%) horses were due annual booster vaccination at the time of developing clinical signs. Main limitations: The interpretation of laboratory results followed a delay in veterinary intervention. Conclusions: Annual booster vaccination should not be relied on as the sole preventative measure against EI. The findings of this study suggest that increasing the frequency of booster vaccinations may be beneficial particularly in young horses and that synchronised scheduling of vaccination regimes across racing yards may contribute to high‐risk periods for EI virus (EIV) transmission.